2020
DOI: 10.1145/3379340
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dynamics of Public Opinions on Twitter

Abstract: Recently, social media has been considered the fastest medium for information broadcasting and sharing. Considering the wide range of applications such as viral marketing, political campaigns, social advertisement, and so on, influencing characteristics of users or tweets have attracted several researchers. It is observed from various studies that influential messages or users create a high impact on a social ecosystem. In this study, we assume that public opinion on a social issue on Twitter carries a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Berne-Manero and Marzo-Navarro [19] show that not only television commercials but also social media commercials can change adolescents' behavior. Naskar et al [20] also agree with this opinion. The research of Zollo et al [21] and Gratiela [22] demonstrates that cognitive, personal integration, and social integration benefits mediate the relationship between the marketing impact of social media advertising and consumer brand awareness.…”
Section: Literature Reviewsupporting
confidence: 56%
“…Berne-Manero and Marzo-Navarro [19] show that not only television commercials but also social media commercials can change adolescents' behavior. Naskar et al [20] also agree with this opinion. The research of Zollo et al [21] and Gratiela [22] demonstrates that cognitive, personal integration, and social integration benefits mediate the relationship between the marketing impact of social media advertising and consumer brand awareness.…”
Section: Literature Reviewsupporting
confidence: 56%
“…For example, Alduaiji and Datta [2] conducted a sentiment analysis on three different Twitter data sets and found that positive tweets are shared more often than negative tweets. Others have found that people's emotional reactions to a topic can change over time [28] and be influenced by the emotions of others [12,20]. In short, social media can convey and evoke emotion.…”
Section: Theoretical Background 21 Role Of Emotion In Social Mediamentioning
confidence: 99%
“…The APIs provided by the social network can easily and conveniently obtain structured data. So Naskar et al [Naskar, Singh, Kumar et al (2020)] use the Search-API provided by Twitter to analyze the emotional dynamics of users' comments on an event or topic on Twitter. Unfortunately, concerning some social networks, such as Facebook, Twitter, Weibo, etc., limited access token dates, API data content, and access times can significantly hamper data collection.…”
Section: Data Crawlingmentioning
confidence: 99%